Kinetics and mechanisms of alcohol dehydration pathways on alumina materials. Issue 17 (27th June 2016) - Kang, Minje; Bhan, Aditya
Abstract : Ethanol dehydration on α, γ, η-alumina mechanistically and kinetically described by the same rate expression implicating similar active sites on all alumina materials. Abstract : The steady state rates of ethene and diethyl ether formation in parallel ethanol dehydration reactions at 573 and 623 K are mechanistically and kinetically described by the same rate expression on different alumina materials (α-, γ-, and η-Al2 O3 ), implying that alumina materials have similar surface sites under reaction environments. In situ chemical titration using pyridine as a titrant elucidates similar site densities (∼0.12 sites nm −2 and ∼0.07 sites nm −2 for ethene formation and ∼0.14 sites nm −2 and ∼0.09 sites nm −2 for diethyl ether formation on γ- and η-Al2 O3, respectively) on γ- and η-Al2 O3 indicating that similar surface features exist on both γ- and η-Al2 O3 . Pyridine-ethanol co-feed experiments show that pyridine inhibited the formation of ethene to a greater extent than diethyl ether suggesting that the two parallel dehydration reactions are not catalyzed by a common active site.